KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DAN KEMANDIRIAN BELAJAR PESERTA DIDIK DENGAN MODEL PEMBELAJARAN INQUIRI - Eliza, Rivdya; Susilawati, Fenny (Math Educa Journal, 2019)
The aim of this study is  to determine the ability of mathematical concepts and self regulated learning of students when teach by inquiry learning models  in class VII SMPN 1 Lembah Gumanti, Solok Regency. The type of this research is Quasy Experiment with Randomized Control Group Only Design research design. Data analysis for the ability to understand mathematical concepts is done by t test, the results obtained are t_calculate (1.85)> ttable (1.68) at an interval of 95% confidence. Because t_count> t_table, H_0 is rejected and H_1 is accepted. Continued data analysis for self regulated learning questionnaire done by non-parametric test obtained H_a (0.214)> H_0 (0.05) then H_0 was rejected and Ha was accepted. It can be concluded that the ability to understand mathematical concepts and the learning independence of students taught with inquiry learning models is higher than the learning independence of students taught with conventional learning models.